RETRACTED: Shear Strength Behavior of Crude Oil Contaminated Sand-Concrete Interface - Amir Hossein Mohammadi; Taghi Ebadi; Mehrdad Ahmadi; Arash Aliasghar (Civil Engineering Journal, 2016)
This article has been retracted: please see Civil Engineering Journal policies: (https://www.civilejournal.org/index.php/cej/about/editorialPolicies).This article has been retracted at the request of the Editor-in-Chief. It has come to our attention that there is significant duplication of text and content between this Civil Engineering Journal article and other paper by the same authors, "Shear Strength Behavior of Crude Oil Contaminated Sand-Concrete Interface" by Amir Hossein Mohammadi, Taghi Ebadi, Abolfazl Eslami, Geomechanics and Engineering (Techno Press) (Volume 12, Number 2, February 2017, pages 211-221) www.techno-press.org/content/?page=article&journal=gae&volume=12&num=2&ordernum=3. One of the conditions of submission of a paper for publication is that authors declare explicitly that the paper is not under consideration for publication elsewhere. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.